Comparative analysis of various oxygen production techniques using multi-criteria decision-making methods. (February 2023) - Aljaghoub, Haya; Alasad, Shamma; Alashkar, Adnan; AlMallahi, Maryam; Hasan, Ranem; Obaideen, Khaled; Alami, Abdul Hai
Highlights: Highlight the importance of medical oxygen during COVID-19 pandemic. Present medical oxygen generation techniques. Quantify the effect of the pandemic on the global supply chain of oxygen. Using MCDC for various oxygen production technologies. Abstract: The current pandemic has adversely affected oxygen production and supply chain, where oxygen treatment is essential for the emergency treatment protocol of patients infected by the virus. This work reports on various techniques of oxygen generation methods, as well as the challenges facing its production, storage, and transportation. Moreover, this study offers a comparative analysis of various oxygen production techniques using Multi-Criteria Decision-Making Methods (MCDM). Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), in addition to the weighting methodologies, Multiplicative Exponential Weighting (MEW) and Simple Additive Weighting (SAW) are chosen as tools to carry out the statistical analysis and rank the oxygen production methods. The ranking criteria includes cost, performance, environmental impact and safety. Moreover, this paper utilizes the Entropy Weight Method (EWM), Criteria Importance Through Inter-criteria Correlation (CRITIC) method, and the Stochastic Dominance (SD) method to distribute the criteria weights. The results show thar oxygen production using membrane technologies is the optimal technique based on all the provided tools and criteria. as it attained the maximum Entropy and Sd values of 0.548 through the TOPSIS method, and the highest CRITIC value through SAW and MEW methods which were 0.260 and 0.236, respectively.